Multiscale Influences on Persistent Extreme Precipitation Events in North China - Guan, Xiaojun; Gao, Jianyun; Li, Tim; Wang, Lan; Chen, Xiaoxiao (Frontiers in Earth Science, 2022)
The present study classifies regional persistent extreme precipitation events (PEPEs) in North China into two types in accordance with variance contributions of different timescale rainfall variability in boreal summer. For Type 1, PEPEs are dominated by 10-20-day periodicity, and for Type 2 PEPEs are mainly influenced by a 30-60-day mode. Atmospheric circulation anomalies associated with the two types of PEPEs are characterized by a zonal wave train (the EU pattern) in the mid-high latitudes in Type 1 but a meridional wave train (the EAP pattern) in East Asia in Type 2. The common feature of the two types is anomalous southerly on the west edge of the West Pacific Subtropical High (WPSH), which favors anomalous moisture transport into the key region. Additional moisture source for Type 2 is linked to anomalous cross-equatorial flow. Both types of PEPEs result from the combined effect of intraseasonal oscillations in both the mid-high latitudes and the tropics. The impact of ENSO on the two types of PEPEs is investigated. While a La Niña and a neutral SST condition in the preceding winter favor for the occurrence of PEPEs, their subsequent transition in central and eastern equatorial Pacific will determine which of the two types of PEPEs is pronounced.